Correction of the Saddle Nose Deformity Using the “Push Up” Technique - Toriumi, Dean M.; Kovacevic, Milos (Facial Plastic Surgery, 2022)
The saddle nose deformity typically occurs after the loss of underlying septal support with loss of projection of the middle nasal vault. This creates a saddling effect as the upper lateral cartilages contract and forms a dip in the profile. The saddle nose deformity can occur from many different etiologies, including septal hematoma, fracture of the septum after trauma, disruption of the dorsal L-strut support after septoplasty, and metabolic disorders resulting in the loss of septal support. In most cases, the nasal bones remain in their native position creating a discrepancy in dorsal height and deformity. Correction of the saddle nose deformity can be performed using one of the two primary approaches. The most basic option is to simply fill the defect with a cartilage onlay graft (solid graft, diced cartilage and fascia, and so on) to create a normal dorsal line. This approach can be effective in many cases. Over time, the onlay graft may descend and create deformity or become visible. The other approach involves opening the middle nasal vault, placing spreader grafts, and reconstituting the dorsal L-strut, performing septal reconstruction or extracorporeal septoplasty. In this paper, we present our technique of repairing the saddle nose deformity using a “push up” method that preserves the middle vault anatomy and reconstitutes the proper projection of the middle-third of the nose.
Keywords: rhinoplasty; dorsal preservation; saddle nose; push up; rib harvest